Are Parental Relationships Improved if Fathers Take Time Off of Work After the Birth of a Child?. (18th March 2019) - Petts, Richard J; Knoester, Chris
Abstract: Research has begun to examine the consequences of paternity leave, focusing primarily on whether paternity leave-taking increases father involvement. Yet, other consequences of paternity leave-taking have not been considered using US data. This study uses longitudinal data from the Fragile Families and Child Wellbeing Study to examine whether fathers' time off from work after the birth of a child is associated with relationship quality, relationship support, and coparenting quality. We also consider whether these relationships are mediated by father involvement. Results suggest that fathers' time off of work after a birth and length of time off are each positively associated with relationship quality and coparenting quality one year after a child's birth. They are also positively associated with trajectories of relationship quality and coparenting quality over the first five years after birth. Father involvement at least partially mediates these relationships. Overall, this study suggests that the potential benefits of fathers' time off of work after the birth of a child may extend beyond father involvement and may improve parental relationships.